Building Consumer Value, Satisfaction, and Loyalty from an Islamic Marketing Perspective - Hendra Halim; Marwan Ramli; Teuku Meldi Kesuma; M. Ridha Siregar (International Journal of Kita Kreatif, 2026)
This article discusses how consumer value, satisfaction, and loyalty can be developed from the perspective of Islamic marketing. This issue is important because modern marketing practices often position consumers as transactional targets, whereas Islamic marketing requires business relationships based on values, ethics, justice, and public benefit. This article positions Islamic marketing as a conceptual approach that is not only concerned with functional satisfaction, but also with consumers’ spiritual and moral satisfaction. The discussion is conducted through a qualitative literature-based study by examining the concepts of consumer value, satisfaction, loyalty, and Islamic principles such as halal, thayyib, amanah, sidq, adl, ihsan, and maslahah. The discussion shows that consumer loyalty in Islamic marketing is formed through the integration of perceived value, satisfaction with consumption experience, trust in the company, and consistent business practices aligned with sharia principles.